(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study examined changes in cervical and shoulder joint range of motion and adverse effects after performing exercises with varying repetitions on patients with cervical spondylosis. Subjects and methods: This cross-sectional study was conducted from November 2023 to May 2024. The research involved a convenience sample of 120 patients aged 18 and older, all of whom had been diagnosed with cervical spondylosis at the Rehabilitation and Occupational Diseases Hospital. The patients were divided into 4 groups, each performing joint exercises for the neck and shoulders at varying repetitions. The range of motion will be assessed using a standardized AI-integrated photogrammetry system designed for evaluation purposes. Results: The group performing cervical joint exercises 3 times and shoulder joint exercises 3 times did not show statistically significant differences compared to the group performing cervical joint exercises 3 times and shoulder joint exercises 5 times. The group performing cervical joint exercises 5 times and shoulder joint exercises 3 times exhibited no statistically significant difference compared to those performing cervical joint exercises 5 times and shoulder joint exercises 5 times. Conclusion: Performing neck and shoulder exercises 3 times each resulted in fewer adverse effects, so this method can be recommended for patients with cervical spondylosis. The group performing neck, shoulder exercises three times each experienced the fewest adverse effects.